A rare case of numerous thoracolithiasis with chest discomfort. (2018) - Kang, Noeul; Choi, Yeonseok; Im, Yunjoo; Choe, Junsu; Kim, Jhingook; Han, Joungho; Kim, Tae Jeong; Kim, Hojoong
Abstract: Thoracolithiasis is a rare benign condition with mobile free bodies in the pleural cavity. It is asymptomatic and mostly found incidentally. Up to our knowledge there is no report of symptomatic numerous thoracolithiasis. We report a very rare case of thoracolithiasis in a 36-year-old female with chest discomfort. Images from computed tomography presented a chain of small non-enhancing nodules in the left hemi-diaphragmatic pleura. Exploratory thoracoscopy was performed and twenty-five mobile pearl like thoracolithiasis were discovered. Histopathology showed extensive necrotic fatty tissue at its center surrounded by fibrosis. The patient was symptom-free after the surgical removal of numerous thoracolithiasis, suggesting thoracolithiasis was associated with chest discomfort.